Removal effects of different emergent-aquatic-plant groups on Cu, Zn, and Cd compound pollution from simulated swine wastewater. (15th October 2021) - Wang, Wei; Cui, Jian; Li, Jinfeng; Du, Jinmeng; Chang, Yajun; Cui, Jianwei; Liu, Xiaojing; Fan, Xiangyang; Yao, Dongrui
Abstract: Aquatic plants play effective in removing heavy metal (HM) as a prominent factor of bioremediations, however, there are still knowledge gaps in species selection and configuration for high removal efficiency (RE) of compound HM and ornamental value. In this study, seven emergent-aquatic-plant species were configured into seven groups and planted in a simulated swine wastewater (SW) with Cu, Zn, and Cd for 75 days in summer. REs of Cu, Zn, and Cd were 45.06–86.93%, 42.40–87.22%, and 73.85–85.52% at day 75, respectively. Higher REs were observed from day 30–45 for Cu and Zn, whereas days 15–30 for Cd. The synergistic removal of Zn and Cu or Zn and Cd was almost observed (p < 0.05). The configuration of G5 ( S. tabernaemontani, I. sibirica, and P. cordata ) was generally efficient roles in the removal at day 45, with REs of 85.14%, 87.06%, and 83.56% for Cu, Zn, and Cd, respectively. The dry weight of roots, water NH4 + -N, temperature, pH, and dissolved oxygen acted on heavy-metal removal. During days 45–75, concentrations of Cu, Zn, and Cd in G5 were 0.52–0.66, 0.54–0.65, and 0.23–0.33 mg L −1 . The former two were below the limits of Grade Ⅱ (1.0 mg L −1 ) and the latter was above the limits of Grade Ⅴ (0.1 mg L −1 ; GB3838-2002). Thus, G5 could be optimal for Cu and Zn removal from simulated SW, however, efficient Cd removal is required to ensure efficient SW recycling. Highlights: Compound HMs almost exist in SW, restrict SW reuse, and threaten human health. REs of compound HMs were estimated and assessed under seven EAP groups. The optimal configuration was the group of S. tabernaemontani, I. sibirica, and P. cordata. Selected EAP configuration was proposed to plant about 45 days in summer. Further steps should be taken for Cd removal with EAPs for SW recycles.